Perfeccionamiento del diseño de transmisiones por engranajes cilíndricos de dientes rectos interiores - Ana María Becerra Ferreiro; Jorge Laureano Moya Rodríguez; Roque Martínez Ortiz; Salvador Gómez Jiménez (Revista Científica, 2012)
his paper presents research results of the article that bears his name. In this regard, the gears have cylindrical inner spur have their peculiarities with respect to the spur gear outer cylindrical in their geometry and cha- racteristics of the contact duration. These gears are subject to the same types of failures that the helical external spur, but the product of the geo- metry and shape of the tooth these failures are less frequent than in the outdoors. In this paper we study the particular characteristics of the con- tact in the helical internal spur, analyzing issues such as: Contact stress coefficient coating and influence of the correction of teeth in reducing failures of these gears.